Impact of narcissistic leadership on employee work outcomes in banking sector of Pakistan - Muhammad Asrar-ul-Haq; Talha Anjum (Future Business Journal, 2020)
Narcissism has been studied as a positive as well as a negative trait. It is a personality disorder in which a person is preoccupied with power, self and vanity. Narcissists often pursue leadership and work for their personal interests which ultimately affect others' well-being. It affects employee performance and leads toward turnover. The purpose of this study is to examine how narcissistic leadership can impact subordinates' job-related outcomes.
Keywords: 650; Job satisfaction; Leadership; Narcissism; Stress; Turnover; Well-being